Carbon monoxide poisoning in a diver. Issue 1 (March 1992) - Allen, H
Abstract : Carbon monoxide poisoning is a well recognized, but uncommon hazard of sport and inshore diving, which occurs either as a result of a faulty air compressor or from air contamination by the exhaust of nearby petrol engines. The incidence of carbon monoxide poisoning may be under-reported as it may mimic decompression sickness, and respond to the same treatment i.e. hyperbaric oxygen.